Terrorismo religioso no quadro da psicologia social - Almeida, Bernado Corrêa d' (2016)
The main objective of this article is to analyze and to understand the phenomenon of terrorism and, particularly, the religious type in the context of social psychology. The article reveals the essence of the phenomenon of terrorism and presents an explanation: the theory of reducing uncertainty. As we look at religious terrorism and its paradox (love of neighbor and antisocial zeal), it is clear that science, politics and religion have to come together and interactively be instructed by social psychology, for a better understanding of social phenomena, particularly, of intergroup and intragroup relations, in view of a better human coexistence.